2021
DOI: 10.4103/2045-9912.311489
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane versus halothane for induction of anesthesia in pediatric and adult patients

Abstract: Induction of anesthesia using an inhalation agent remains a fundamental technique due to its rapid induction and emergence. Sevoflurane is preferred over halothane for its faster induction of anesthesia and lesser complications. Studies on sevoflurane in pediatrics have established it as safe and effective. However, its effectiveness in adults is very limited. Hence, this study was conducted to compare the induction and intubating conditions, hemodynamic profiles, and emergence from anesthesia with sevoflurane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Due to rapid induction and small tissue uptake, the patient recovered quickly after surgery. Studies have confirmed that patients under sevoflurane anesthesia generally recover less than 10 minutes after drug discontinuation, and patients have no symptoms of falling asleep again after waking up, and there are obvious complications such as nausea and vomiting, dizziness, headache, cough, throat and bronchospasm, edema, and other complications [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to rapid induction and small tissue uptake, the patient recovered quickly after surgery. Studies have confirmed that patients under sevoflurane anesthesia generally recover less than 10 minutes after drug discontinuation, and patients have no symptoms of falling asleep again after waking up, and there are obvious complications such as nausea and vomiting, dizziness, headache, cough, throat and bronchospasm, edema, and other complications [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…McKinney et al [ 3 ] discovered that prominent leptomeningeal contrast enhancement (pLMCE) can occur in pediatric patients who are under anaesthesia with propofol. However, in clinical practice, the administration of sevoflurane has become a common anaesthetic practice for pediatric patients undergoing magnetic resonance imaging (MRI) due to advantages such as rapid induction and recovery[ 4 ]. Nevertheless, whether sevoflurane can also induce pLMCE remains a scientific question that needs resolution.…”
Section: To the Editormentioning
confidence: 99%
“…Animals were randomly divided into three groups by blinded experimenters. 0.2 mL/kg of the anesthetic combination (ketamine HCl, 150 mg/1.5 mL; xylazine HCL, 30 mg/1.5 mL; and distilled water, 1 mL) was subcutaneously injected before surgery to reduce animals' pain as reported in the study by Kanat et al 14 The animals were fixed in a stereotactic frame (Stoelting Co., Wood Dale, IL, USA). Volatile anesthetic sevoflurane was administered using a modified anesthesia unit.…”
Section: Ethodsmentioning
confidence: 99%
“…Mean induction time was assessed based on the time interval between the placement of the face mask and the loss of eyelash reflex. 14 As the mean induction time was found to be 135 seconds, the higher value of 165 seconds was accepted as a late induction time. The instant when the first signs of inactivity appeared was recorded to estimate the depth of anesthesia.…”
Section: Ethodsmentioning
confidence: 99%